A new species of the genus Boulenophrys (Anura: Megophryidae: Megophryinae) from Jiulianshan National Nature Reserve, southern Jiangxi, China - Wang, Hao-Tian; Wu, Xiao-Gang; Song, Han-Ming; Huang, Zhong; Zhuo, Xiao-Hai; Wang, Ying-Yong (Zootaxa, 2025)
A new species of the genus Boulenophrys (Anura: Megophryidae: Megophryinae), Boulenophrys huangniushiensis sp. nov., is described from Jiulianshan National Nature Reserve, Jiangxi Province, southeastern China. The new species was identified based on a combination of morphological characteristics and molecular phylogenetic analyses based on mitochondrial 16S rRNA and CO1 genes. Phylogenetic results place the new species in a well-supported clade with B. xiangnanensis and B. yingdeensis, though it exhibits substantial genetic divergence from both. Morphologically, the new species is distinguishable by its moderate male body size (SVL 37.9–40.7 mm), absence of vomerine teeth, and toes without lateral fringes and webs. The discovery adds to the growing diversity of Boulenophrys and represents the third species of the genus recorded from this biodiversity-rich nature reserve.